Developmental Changes in Epistemological Beliefs in 9-Year-Old Student - Mahdavieh, Mahin; Hashemi, Soheila; Naderi, Habibollah; Firouzjaiyan, Ali Asghar (Iranian Journal of Educational Sociology, 2022)
Purpose: Epistemological beliefs mean what people believe about the nature of knowledge and knowing that can be related to areas such as learning and theory of mind.The purpose of the present study was to investigate the growth of epistemological beliefs in 9-year-old girl children.Methodology: This was a qualitative grounded theory study. The study population consisted of elementary third grade girl students in Babolsar city in 1397. A sample of 20 students through purposeful sampling method with Theoretical saturation was selected and the epistemological beliefs of these participants were examined in two stages over a period of one year. The research tool was in-depth interviews with emphasis on "draw, write, tell" technique which was used in both stages. Coding was also used to analyze the data.The validity of the findings was evaluated by triangulation method including expert review, continuous comparison of data and different methods of data collection.Findings: The epistemological beliefs of children emerged in five dimensions, including ' Ownership ', ‘Innateness’, ' Exactness', 'simplicity' and ‘pace’. Each of these dimensions was relatively complex, and developed over a period of one year, especially in dimension of ownership.Conclusion: Based on the findings, it can be said that the development of girl children's epistemological beliefs towards more complex beliefs can occur if necessary conditions are in instructional Environments. Therefore, it is suggested that providing children with appropriate learning environments such as constructive learning environments and opportunities to reinforce the power of reasoning and argumentation.